Assessing the Viability of Algal Biodiesel as a Supplement to Liquid Fossil Fuels in Uganda - Marvin Aheebwa Ashaba (Uganda Christian University, 2025)
Uganda faces energy security, open economies and environmental degradation due to heavy reliance on fossil fuels. This study investigates the viability of algal biodiesel as a supplement to liquid fossil fuels, leveraging Uganda's tropical climate. Three species of algae, namely Botryococcus braunii, Nannochloropsis sp., and Chlorella vulgaris, were evaluated under optimised conditions for species compatibility, lipid extraction yield, and biodiesel quality. Results indicated that Chlorella vulgaris is the most suitable species for decentralized systems, as it displayed the highest growth rate (13.4 cm biomass on Day 12) and a moderate lipid yield (20–30%). Diethyl ether-isopropanol achieved the highest yield at 83.1% but posed safety concerns, while hexane-isopropanol represented the best compromise between viability and effectiveness. The biodiesel characteristics partially met ASTM requirements; viscosity (2.82 mm²/s) and density (0.8335 g/cm³) were compliant, but cetane values of 5.2 required blending with petrodiesel (B20). Algal biodiesel is techno-feasible in Uganda, benefiting from low-cost open-pond systems, cooperative models at the community level, and the integration of wastewater treatment to address energy poverty, promote environmental sustainability, and support a circular economy concept.
Undergraduate research